Hybrid molecules of scutellarein and tertramethylpyrazine's active metabolites for ischemic stroke. Issue 19 (1st October 2019) - Dong, Yongxi; Zhang, Xiaohe; Liu, Mingji; Yang, Yang; Guo, Ting; Mao, Yuanhu; Zhang, Jiquan; Fu, Xiaozhong; Zhao, Yonglong; Chen, Jinglei; Dong, Li; Qiao, Chunhua
Graphical abstract: Abstract: A series of hybrid molecules of scutellarein and tertramethylpyrazine's active metabolites have been synthesized. Compared to the original compound, these prepared compounds exhibited higher water solubility, more appropriate logP and better stability. Importantly, compounds 11b, 11d and 11e showed improved neuroprotective activity against the H2 O2 -induced cell death in PC12 cells, and better antithrombosis activity. The optimized compound 11b was further evaluated by cerebral ischemia/ reperfusion in the middle cerebral artery occlusion (MCAO) model, the results showed that the compound could significantly reduce the infarct area and decrease the neuronal cell damage in CA1 pyramidal neurons. Overall, we demonstrated that the twin drug strategy could be applied in the development of agents for the treatment of ischemic stroke.